Socialization Of The Characteristics Of Oil That Is Used Repeatedly For The People Of Ranah Batahan District - Syukri, Daimon; Sepnita, Widia (Institute of Research And Community Service, Andalas University / LPPM Universitas Andalas, 2023)
In this activity, food safety outreach was carried out regarding the use of cooking oil for repeated frying. Cooking oil is a triglyceride compound which has a high boiling point. The use of cooking oil in society is often used repeatedly. This means that the chemical content in cooking oil can undergo oxidation and hydrolysis processes so that the quality of the oil becomes damaged. The formation of peroxide compounds means that oil will become a precursor to the formation of an unhealthy condition for those who consume it. Therefore, this socialization was carried out to increase public knowledge. The socialization activities were carried out during real work lecture activities for Andalas University students for the 2023 period. The socialization was carried out using the lecture and question and answer method. As a result of this activity, it is known that there has been an increase in community knowledge, which is indicated by the establishment of very good communication activities between the community and the real work lecture team from Andalas University. It is hoped that this activity will be carried out again with a different food safety topic.